Embryonic reprogramming of the tumor vasculature reveals targets for cancer therapy - Elisabeth J. M. Huijbers; Judy R. van Beijnum; Karlijn van Loon; Christian J. Griffioen; Richard Volckmann; Ayse Bassez; Diether Lambrechts; Madalena Nunes Monteiro; Connie R. Jimenez; Pancras C. W. Hogendoorn; Jan Koster; Arjan W. Griffioen (Proceedings of the National Academy of Sciences, 2025)
A sustained blood supply is critical for tumor growth, as it delivers the nutrients and oxygen required for development. Targeting of blood vessel formation via immunotherapies is an area of great importance. Knowing that certain embryonic genes, such as carcinoembryonic antigens (CEA) and oncofetal fibronectin, become reexpressed in malignant transformation, we hypothesized that a similar phenomenon holds true for tumor endothelial cells (TECs) as well. An approach for identification of highly selective tumor endothelial markers was conducted to develop targeted antiangiogenic immunotherapies. We first queried the transcriptome that is present during embryo development. We then performed a systematic search for genes selectively expressed in the mouse embryo at days E11 and E18, as compared to the transcriptome of the adult mouse. Subsequently, we queried for expression of these embryonic genes in sorted murine TECs. This approach identified among others the tumor endothelial antigens fibrillin-2 (Fbn2), elastin microfibril interface-located protein 2 (Emilin2) as well as the tumor endothelial antigens lysyl oxidase (Lox) and serine/cysteine protease inhibitor, clade E, member 1 (Serpine1; Pai-1). For these selected genes, functional involvement in angiogenesis was confirmed in in vitro bioassays. We subsequently used iBoost conjugate vaccine technology to develop vaccines against the selected targets. For all four targets, vaccination readily induced target-specific antibody responses in mice, resulting in inhibition of tumor growth. Access to highly specific tumor endothelial markers provides opportunities for direct targeting of the tumor vasculature with high specificity, without affecting healthy vasculature.